Business Tax Incentives and Investments - Thomas Karier (Levy Economics Institute of Bard College, 1994)
For more than twenty years, U.S. tax policy offered businesses a credit based on a percentage of investment in equipment. The stated purpose of the investment tax credit was to encourage investment as a means to further modernization, job growth, and competitiveness. The results of this study, however, indicate that investments were not significantly higher when the credit was in force than during periods when it was not. While the credit may have increased the rate of return on equipment investments, additional tests fail to find an increase in investment spending due to this particular incentive. The results also suggest that only a small fraction of additional corporate income generated by the credit was likely to have been spent on investment. Given the need to encourage investment spending, especially during recessions, alternatives to investment tax credits should be pursued. A logical alternative is a broader program of public investment in education, infrastructure, and research.
Keywords: 330